Digital processing of photos from a 4π track detector - Afanasiev, S.N.; Afanasieva, I.A. (Problems of Atomic Science and Technology, 2022)
A measuring complex with a digital data bank of stereo photos of photonuclear reactions on ⁴He, ¹²C, ¹⁴N, and ¹⁶O nuclei got from a 4π track detector has been created. The file name was formatted into a certain type of record, which included information about the experiment and the position in the data bank. A graphical application was presented that allowed semi-automatic determination of points along tracks of different lengths and curvatures. Methods and algorithms allowing to transfer into the camera system and perform event reconstruction were developed. Additional programs for the physical analysis of the reconstructed events and the graphical representation of the obtained results were created.